Climate negotiations from Lima to Paris - Acurio, Rómulo (2015)
Climate negotiations under the UNFCCC head this year towards the Paris deadline to adopta new legally-binding and universal agreement. This article summarizes the outcomes from the Lima Conference (December 2014), which laid the grounds for negotiations this year, and identifies the most sensible political issues currently addressed by this complex process. It also highlights some objectives and priorities of the Peruvian Presidency of COP20.